Multiple catalytic aldolase antibodies suitable for chemical programming - Goswami, Rajib Kumar (2009)
Chemical programming of nine murine antibodies with catalytic aldolase activity was examined using compounds, equipped with diketone or pro-vinyl ketone linkers that inhibit integrin adhesion receptor functions. The results showed that most Abs were programmed using the diketone compounds in a manner similar to previously reported catalytic antibody 38C2. On the other hand, only those antibodies, which catalyzed the retro aldol reaction of the pro-vinyl ketone linkers efficiently, were programmed. Conjugated to integrin targeting compounds, at least three new antibodies, including 84G3, 85H6, and 90G8, exhibited high specific binding to human tumor cells expressing integrin α(v)β(3).